Study of the interactions of bovine serum albumin with a molybdenum(II) carbonyl complex by spectroscopic and molecular simulation methods - Jeremias, Hélia F. (2019)
Therapy with inhaled carbon monoxide (CO) is being tested in human clinical trials, yet the alternative use of prodrugs, CO-Releasing Molecules (CORMs), is conceptually advantageous. These molecules are designed to release carbon monoxide in specific tissues, in response to some locally expressed stimulus, where CO can trigger a cytoprotective response. The design of such prodrugs, mostly metal carbonyl complexes, must consider their ADMET profiles, including their interaction with transport plasma proteins. However, the molecular details of this interaction remain elusive. To shed light into this matter, we focused on the CORM prototype [Mo(η 5 -Cp)(CH 2 COOH)(CO) 3 ] (ALF414) and performed a detailed molecular characterization of its interaction with bovine serum albumin (BSA), using spectroscopic and computational methods. The experimental results show that ALF414 partially quenches the intrinsic fluorescence of BSA without changing its secondary structure. The interaction between BSA and ALF414 follows a dynamic quenching mechanism, indicating that no stable complex is formed between the protein Trp residues and ALF414. The molecular dynamics simulations are in good agreement with the experimental results and confirm the dynamic and unspecific character of the interaction between ALF414 and BSA. The simulations also provide important insights into the nature of the interactions of this CORM prototype with BSA, which are dominated by hydrophobic contacts, with a contribution from hydrogen bonding. This kind of information is useful for future CORM design.